Effect of cattle manure ash on strength, workability and water permeability of concrete. (1st June 2015) - Zhou, Shuguang; Tang, Wenhui; Xu, Peng; Chen, Xinxiao
Highlights: Cattle manure ashs on strength, workability and permeability of concrete is studied. Influence of three cattle manure ashs on the mixing way of the concrete is studied. Mechanical mixing and vibration is the optimum when CMA is used in concrete. Character of the CMA-M (combustion temperature 500 °C) concrete display the best. Abstract: Combustion is an attractive method for cattle manure waste disposal since it produces heat and electrical energy and minimizes groundwater and air pollution by consumption of the waste. A major problem arising from the combustion of cattle manure waste is the significant resultant quantity of cattle manure ash (CMA). In this paper, we study the strength, workability and water permeability of concrete when CMA is used as a partial replacement in cement. Three types of CMA were tested, namely CMA, CMA-M and CMA-U, which were generated after combustion at 200 °C, 500 °C and 800 °C. The strength of concrete that contained CMA was determined using cubic samples (100 mm edge) at 7, 28 and 56 days. The workability was measured from the slump when the concrete was mixed manually or mechanically. The water permeability, including percentage, velocity and coefficient of water absorption of concrete, was determined at 7, 28 and 90 days using an improved initial surface absorption test. The workability increased from CMA to CMA-M to CMA-U. The compressive strength increased with increasing particle size from CMA to CMA-M but decreased from CMA-M to CMA-U. The water permeability, including percentage, velocity and coefficient, increased from CMA to CMA-M to CMA-U at 7 and 28 days. At 90 days, the water permeability, including percentage, velocity and coefficient of water absorption of CMA-M concrete, were the lowest in the three CMA concretes. CMA-M was the best material in terms of its overall workability, strength and water permeability. Mechanical concrete mixing and vibration was the optimal preparation procedure. CMA can therefore be blended with cement for concrete production depending on the ultimate use.